Conservation through connection: Approaches to engaging communities in applied grizzly bear research - Hughes, Courtney; Elmeligi, Sarah; Morehouse, Andrea (Frontiers in Conservation Science, 2022)
Human-wildlife dynamics is a growing field and one of considerable importance to conservation. Wild spaces are in short supply, and consequently wildlife and people increasingly share the landscape, though not necessarily by choice. As a result, peoples’ needs might not be prioritized over those of wildlife, even in cases of human-wildlife conflict. For wildlife conservation to be effective and human-wildlife coexistence possible, the needs of both wildlife and people must be simultaneously addressed. Rather than an afterthought or a sentence in the conservation/management implications section of a paper, community engagement should be addressed before, during, and after a research project. However, this can be a difficult and often complicated task, for multiple reasons. Building relationships founded on trust, respect and reciprocity with community members takes commitment, time, skill, and a willingness by researchers to be open-minded in terms of methodologies and new ideas. Different cultural norms, beliefs, perspectives and biases can further exacerbate these challenges. Here, we share three short case studies reflecting our own research experiences engaging with communities in the field of grizzly bear (Ursus arctos) ecology and conservation science. We conclude with guidelines for advancing effective community engagement and suggestions for tackling some common barriers. Overall, we offer considerations for a practical and more holistic approach to large carnivore conservation, established on a foundation of strong community support.